Pengaruh Gaya Kepemimpinan Terhadap Kompensasi dan Loyalitas Karyawan di Kota Cirebon - Kartika Putri, Oktalina; Agnu Dian Wulandari, Oryz; Fauzi, Feri (Awatara Publisher, 2025)
This study aims to analyze the influence of Leadership Style on Employee Compensation and Loyalty in Cirebon City. Using a quantitative approach with the Structural Equation Modeling Partial Least Square (SEM-PLS) method, 100 employee respondents from various sectors in Cirebon were sampled. The results showed that Leadership Style had a significant effect on Compensation (T-statistic = 16.724; p-value = 0.000) and Employee Loyalty (T-statistic = 18.757; p-value = 0.000). This finding indicates that an effective leadership style not only increases perceptions of compensation fairness but is also able to foster employee loyalty in the long term. Theoretically, these results support the Path-Goal Theory which emphasizes the importance of the role of leaders in facilitating the needs of their subordinates. Limitations in this study include limited geographic scope, small sample size, and the absence of mediating or moderating variables analyzed. Further research is recommended to expand the scope of the region, increase the number of respondents, and integrate additional variables to obtain a more holistic understanding. This research provides practical contributions to organizations in designing leadership strategies that support increased employee loyalty.